Study on methods to extract high contrast image in active dynamic thermography - Saxena, Ashish (2020)
In the present study, image reconstruction methods are applied in active dynamic thermography (ADT) to visualize the superficial blood vessel with high contrast. ADT is performed on the left forearm of a human subject by applying cooling based external thermal stimulation. Both non-parametrized, viz. sequence image, sequentially subtracted image, Discrete Fourier Transformation (phase and amplitude image), and Thermographic Signal Reconstruction (TSR), and parametrized, viz. Tau time (τ), dTnorm, t90−10n, and Tissue Activity Ratio (TAR), types of image reconstruction methods are used. To perform a quantitative comparison, among the image reconstruction methods, the image contrast value is evaluated. While sequentially subtracted image provides a high contrast image in non-parametrized image reconstruction methods, for parametrized image reconstruction methods, it is TAR. Among all the methods considered, TAR provides the best contrast image followed by τ image method.